Direction of Trade Statistics Yearbook, 2015. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper presents the 2015 yearbook of the Direction of Trade Statistics (DOTS). Quarterly issues of this publication provide, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The yearbook provides, for the most recent seven years, detailed trade data by country for approximately 184 countries, the world, and major areas. The information on exports and imports by trading partners that countries report to the Fund varies in terms of frequency and currentness. In order to provide guidance regarding the sources of the figures for individual countries, figures in the country, world, and area pages are shown with symbols to the right of the figure. Country pages include lines for all partner countries that have been reported, estimated, or extrapolated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice